Pengaruh Disiplin Kerja, Keselamatan Kerja Dan Kesehatan Kerja Terhadap Produktivitas Karyawan Pada PT. Teluk Luas Kota Padang - Ahyar Ahyar; Vicky Brama Kumbara; Chintya Ones Charly (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
AHYAR, 20101155310152, Department of Management in 2020, The Effect of Work Discipline, Occupational Safety and Occupational Health on Employee Productivity. This study aims to examine how much influence work discipline, occupational safety and occupational health have on employee productivity at PT. Teluk Luas Kota Padang. The method of collecting data through surveys and circulating questionnaires, with a population of 125 people sample 125 respondents obtained from the teknics saturated sample Formula. The analysis method used is path analysis using smartpls. The results of the research obtained based on the Partial Test There is a positive and significant influence between Work Discipline on Employee Productivity. There is a positive and significant influence between Work Safety and Employee Productivity. There is a positive and insignificant influence between Occupational Health and Employee Productivity.